Time Course of Perceived Visual Distortion and Axial Length Growth in Myopic Children Undergoing Orthokeratology - Liu, Guihua; Wu, Yiyuan; Bi, Hua; Wang, Biying; Gu, Tianpu; Du, Bei; Tong, Jianliang; Zhang, Bin; Wei, Ruihua (Frontiers in Neuroscience, 2021)
Purpose: To establish the time course of the subjective visual function changes during the first month of orthokeratology treatment in myopic children, and to investigate how the time course variations are associated with the objective optical quality changes and the axial length growth (ALG) after one year of treatment. Methods: A total of 58 myopic children aged from 8 to 16 years participated in this self-controlled prospective study. All subjects were fitted with designed spherical four-zone orthokeratology lenses. Subjective visual function was evaluated with orientation discrimination threshold (ODT), and objective optical quality was quantified with the high-order aberration root-mean-square (HOA-RMS) and the changing speed of HOA. The measurements were done before the lens fitting and one day, 1-, 2-, and 4-weeks after lens wear. Axial length was obtained at baseline and 1-year follow-up, and ALG was defined as the difference. One-way ANOVA was conducted to compare the difference for statistical analysis. Results: After lens fitting, the ODT time courses peaked on day one in 28 children, one week in 15 children, two weeks in 11 children, and four weeks in 4 children. In contrast, the HOA-RMS steadily rose during the first month, and the changing speed of HOA was only transiently elevated on day one after the initial lens wear. The ALG was 0.12 ± 0.20 mm in subjects whose ODT peaked at day one, 0.08 ± 0.09 mm in subjects whose ODT peaked on 1-week, and 0.12 ± 0.15 mm in subjects whose ODT peaked on 2-week or later. There was no difference in axial growth among the subjects whose ODI peaked at different days (P = 0.734). Conclusion: While half ODT time course resembled the changing speed of HOA with a transient elevation on day one, about a quarter of the ODT time course resemble the steadily rising of HOA-RMS, and the rest was located in the middle. The ALGs in children with different types of ODT time courses were similar.